Contenido de compuestos fenólicos totales y capacidad reductora de la cáscara de musa sp. “plátano - Veliz Quezada, Cristian Alexander (2016)
Total phenolics contents and reducing capacites of peels from two Musa sp. “banana” were studied. The total phenolics contents and reducing capacities were determined by the Folin-Ciocalteu method and the 1,1-diphenyl-2-picrilhidracilo (DPPH•) radical scavenging assay, respectively. The highest total phenolic content 41.69 ± 0.30 mg GAE/g dry weight and the less median reducing concentration (RC50) 19.39 ± 0.007 mg/mL was obtained from the freeze-dried extract of peel of Musa paradisiaca L. A relatively high inverse correlation between total phenolics contents and median reducing concentrations (RC50) was obtained from the freeze-dried extract of peels of two Musa sp. “banana” (r = -0.995, p < 0.01), therefore phenolics of peels of Musa sp. banana have good reducing capacity